Time trends of thyroglobulin antibody in ablated papillary thyroid carcinoma patients: Can we predict the rate of negative conversion?. (April 2019) - Song, Eyun; Ahn, Jonghwa; Oh, Hye-Seon; Jeon, Min Ji; Kim, Won Gu; Kim, Won Bae; Shong, Young Kee; Baek, Jung Hwan; Lee, Jeong Hyun; Ryu, Jin Sook; Chung, Ki Wook; Hong, Suck Joon; et al.
Highlights: Positivity for preoperative TgAb in patients with PTC is higher than general population. The higher the TgAb levels at the time of postoperative ablation, the longer it takes to negative conversion. TPOAb status at the time of ablation is also associated with the time required for the disappearance of TgAb. TgAb and TPOAb together can predict the rate of negative conversion of TgAb. Abstract: Objectives: Persistence of thyroglobulin antibody (TgAb) in patients with papillary thyroid carcinoma (PTC) years after total thyroidectomy (TT) followed by ablation occurs even without any evidence of structural disease. Few studies have studied the natural course of TgAb positivity and factors that may influence this course. The present study evaluated the time trends of TgAb in ablated PTC patients and aimed to identify the predictive factors for the rate of negative conversion of TgAb. Materials and methods: Overall, 1279 patients who underwent TT and subsequent ablation for PTC, with available data on thyroid peroxidase Ab (TPOAb) and TgAb prior to surgery (preop-) and ablation (abl-) were enrolled. Patients with initial distant metastasis or recurrence during follow-up were excluded. Results and conclusion: Preop-TgAb was positive in 24.9% of patients (n = 319), whereas abl-TgAb positivity decreased to 12.8% (n = 164). In 164 patients positive for abl-TgAb, TgAb in patients with higher abl-TgAb levels decreased more gradually than those observed in patients with lower abl-TgAb levels (p < 0.001). Furthermore, in patients within the same range of abl-TgAb levels, patients positive for abl-TPOAb had a higher rate of negative conversion of TgAb compared with negative patients for abl-TPOAb (log rank p < 0.001). TPOAb significantly increased the rate of negative conversion in multivariate analysis adjusted for abl-TgAb (odds ratio 1.59, 95% confidence interval 1.11–2.28, p = 0.011). This study clearly showed that abl-TgAb titers and abl-TPOAb status can predict the rate of negative conversion. These findings can guide the optimal timing for additional examination in patients positive for TgAb during follow-up.